Phenotypic detection of Carbapenemase production by combination of Modified Carbapenem inactivation method (mCIM) and EDTA- Carbapenem inactivation method (eCIM) among carbapenem resistant Enterobacterales at a tertiary care teaching hospital of Southern - Anamikavyas, Anamikavyas; jain, Sarita (Journal of Neonatal Surgery, 2025)
Background: Infections caused by Carbapenem resistant organism are well acknowledged for their detrimental effects on both healthcare facilities and patients. These effects include rise in mortality rates, prolonged hospital stays, and increased financial expenses. In addition to this, inappropriate treatment regime worsens the problem of antimicrobial resistance. Carbapenemase production is the most common mechanism of carbapenem resistance, so rapid detection of carbapenemase production is essential to initiate appropriate treatment and to implement appropriate infection control practices to prevent further dissemination. In this study we aimed to identify the carbapenemase producing Enterobacterales by phenotypic methods i.e modified carbapenem inactivation method (mCIM), EDTA- Carbapenem inactivation method (eCIM). Methodology: It was a cross sectional study and data was collected over a period of 8 months in the Department of Microbiology, in a tertiary care teaching hospital of Southern Rajasthan.100 clinical isolates which were resistant to one of the carbapenems (imipenem, meropenem or ertapenem) by Kirby-Baurer disk diffusion method were included in the study. All these isolates were subjected for carbapenemase detection by phenotypic methods i.e modified carbapenem inactivation method (mCIM) and EDTA- carbapenem inactivation method (eCIM) and the result were analysed to find out carbapenemase production as per CLSI 2023. Results: Among 100 CRE isolates, 66% were Klebsiella pneumonia followed by Escherichia coli i.e 34%.Out of these 100 CRE isolates, 94% isolates were mCIM test positive, from which 62% isolates were eCIM test positive. 59%of the total isolates tested were Metallo β-lactamase producers and 35% were serine β–lactamase producers. Conclusion: we would like to conclude that performing mCIM and eCIM methods on carbapenem-resistant isolates as a routine can help clinicians to choose most appropriate treatment regime. Timely identification and the implementation of effective infection prevention and control measures are crucial in reducing the prevalence of carbapenem-resistant Enterobacterales (CRE) among patients